Systematic reappraisal of the anti-equatorial fish genus Microcanthus Swainson (Teleostei: Microcanthidae), with redescription and resurrection of Microcanthus joyceae Whitley - Tea, Yi-Kai; Gill, Anthony C. (Zootaxa, 2020)
The taxonomy and classification of the microcanthid fish genus Microcanthus Swainson has been a subject of contention dating back to the 19th century. Its allopatric, disjunct anti-equatorial distribution across the Indo-West Pacific has resulted in the recognition of several nominal taxa, though these have been widely regarded as synonyms of Microcanthus strigatus (Cuvier). Following the results published in a companion study elsewhere by the authors, the taxonomy of Microcanthus and the validity of these nominal synonyms are herewith revised. Microcanthus strigatus is redescribed on the basis of 66 specimens from East Asia, Hawaii and Western Australia, and M. joyceae is resurrected and redescribed on the basis of 25 specimens from eastern Australia and the southwest Pacific. Microcanthus differs from other microcanthid genera in having the following combination of characters: dorsal-fin rays XI,15–17 (usually XI,16); anal-fin rays III,13–15 (usually III,14); pectoral-fin rays 15–17 (usually 16); scales ctenoid with ctenial bases present; lateral-line scales partially or heavily obscured by adjacent scales; and body pale in preservation with five horizontal dark stripes reaching the posterior edges of dorsal and anal fins, and base of caudal fin. The review is accompanied by a key to the genera of Microcanthidae.